THE DEMISE OF THE ARAL SEA - AN ENVIRONMENTAL DISASTER - Waltham T.; Sholji I. (My University, 2001)
The shrinkage of the Aral Sea ranks as one of the world's greatest man-made environmental disasters. While there is some hope for a separated northern part, the main sea is doomed